Women from Traditional Islamic Educational Institutions in Indonesia Negotiating Public Spaces - Srimulyani, Eka (Amsterdam University Press, 2012)
Until currently there have been no specific publications, particularly in English, on women in traditional Islamic educational institutions in Indonesia, known as pesantren, which played a significant role in shaping the gender issues in the Indonesian Muslim community. This informative and insightful book contributes to two booming fields in Indonesian studies: the study of Islam and the study of Muslim women. It also adds a new perspective to the English-language literature on Muslim women outside the Middle-Eastern or Sub-Indian continent communities context, which used to dominate the scholarly discussion or publication in this field.